2016
DOI: 10.1021/acsami.6b06644
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Photocatalytic Hydrogen Evolution in Ternary Hybrid TiO2/CuO/Cu Thoroughly Mesoporous Nanofibers

Abstract: Development of novel hybrid photocatalysts with high efficiency and durability for photocatalytic hydrogen generation is highly desired but still remains a grand challenge currently. In the present work, we reported the exploration of ternary hybrid TiO2/CuO/Cu thoroughly mesoporous nanofibers via a foaming-assisted electrospinning technique. It is found that by adjusting the Cu contents in the solutions, the unitary (TiO2), binary (TiO2/CuO, TiO2/Cu), and ternary (TiO2/CuO/Cu) mesoporous products can be obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(82 citation statements)
references
References 46 publications
(66 reference statements)
3
79
0
Order By: Relevance
“…On the other hand, the presence of co‐catalyst (CuO or CoO) improves the photocatalytic activity of hydrogen production, due to formation of the p‐n heterojunction that effectively separates charge carriers. It is worth mentioning that CuO and CoO played different roles during the process: while CoO is expected to catalyze the O 2 evolution reaction, CuO is expected to catalyze the H 2 evolution reaction . However, the improvement by coupling ST with CuO is considerably greater than that obtained when the material is modified with CoO, indicating that reduction reaction is the controlling step in the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the presence of co‐catalyst (CuO or CoO) improves the photocatalytic activity of hydrogen production, due to formation of the p‐n heterojunction that effectively separates charge carriers. It is worth mentioning that CuO and CoO played different roles during the process: while CoO is expected to catalyze the O 2 evolution reaction, CuO is expected to catalyze the H 2 evolution reaction . However, the improvement by coupling ST with CuO is considerably greater than that obtained when the material is modified with CoO, indicating that reduction reaction is the controlling step in the photocatalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Except for size control, shape control of particulates on nanometer scale is more difficult and starts to attract attention recently. Many nanomaterials, more specifically anisotropic nanostructures, have been successfully synthesized including nanotubes, nanowires, nanorods, nanofibers, and nanosheets . However, most synthesis methods for these types of particles require multiple, complicated synthesis procedures and are typically nonconductive to be scaled up manufacturing as yields are typically milligram or less quantities of material.…”
Section: Particle Diameter Statistics For Synthesized and Calcined Timentioning
confidence: 99%
“…Titanium is one of the most widely studied and applied catalyst materials in reactions such as water splitting (hydrogen and oxygen evolution reactions) and CO 2 reduction [10,11,12,13,14,15,16,17,18], with the hybridization of two or more materials being employed to increase catalytic activity [17,18,19,20,21,22,23,24]. Roy et al prepared transition metal (Fe, Co, and Cu)-doped TiO 2 nanocrystals and examined their electrochemical oxygen evolution reactions (OERs) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hu et al coated Si, GaAs, and GaP photoanodes with TiO 2 by atomic layer deposition, which prevented corrosion and resulted in continuous O 2 evolution in a 0.1 M KOH solution at photocurrent densities >30 mA·cm −1 and ~100% Faradaic efficiency [21]. Moreover, Hou et al reported that mesoporous TiO 2 /CuO/Cu materials exhibit enhanced photocatalytic H 2 evolution (3.5× higher) compared to commercial mixed phase TiO 2 (Degussa, P25) [22]. Additionally, Terashima reported a p-n heterojunction photoelectrode of boron-doped diamond(p-type)/TiO 2 (n-type) prepared by microwave plasma chemical vapor deposition followed by sputter coating [23].…”
Section: Introductionmentioning
confidence: 99%